Relationships of Plasma Viscosity, Coagulation and Fibrinolysis to Coronary Risk Factors and Angina - Lowe, G D O; Wood, D A; Douglas, J T; Riemersma, R A; Macintyre, C C A; Takase, T; Tuddenham, E G D; Forbes, C D; Elton, R A; Oliver, M F (Thrombosis and Haemostasis, 1991)
Plasma viscosity, molecular markers of activated coagulation and fibrinolysis (fibrinopeptides A and Bβ15-42), coagulation factors (fibrinogen and factor VII) and antiplasmins were measured in 529 men aged 35-54 years and related to new angina pectoris (n = 117) and to coronary risk factors in controls without angina (n = 412). Five major risk factors (cigarette-smoking, blood pressure, cholesterol, triglyceride and body mass index) were each associated with increases in plasma viscosity, coagulation factors, and imbalance of coagulation over fibrinolysis (increased ratio of fibrinopeptide A/fibrinopeptide Bβ15-42). Increased viscosity and fibrinogen in smokers were partly reversed in exsmokers, but the imbalance of coagulation and fibrinolysis persisted. Cholesterol and triglyceride were also associated with increased antiplasmin activity. In men with angina, only fibrinogen was elevated compared to controls. We suggest that increased plasma viscosity and an imbalance of coagulation over fibrinolysis may be mechanisms by which known risk factors promote arterial thrombosis, but are not present in stable angina.